A place to land - Wittenstein, Barry; Pinkney, Jerry (New York : Holiday House, 2019)
"The true story behind the writing of Martin Luther King's "I Have a Dream" speech."--Provided by publisher.
"Neal Porter Books."
Grades K-3.
Ages 6-9.
Keywords: King, Martin Luther, -- Jr., -- 1929-1968. -- Juvenile literature; Speeches, addresses, etc., American -- Washington (D.C.) -- Juvenile literature; African Americans -- Civil rights -- History -- 20th century -- Juvenile literature; Civil rights movements -- United States -- History -- 20th century -- Juvenile literature